Polymer-derived Biosilicate-C composite foams: Phase development and photothermal effect. Issue 16 (December 2021) - Dogrul, Fulden; Bortolin, Stefano; Del Col, Davide; Dengo, Nicola; Pedron, Danilo; Michalek, Martin; Elsayed, Hamada; Galusek, Dušan; Bernardo, Enrico
Abstract: Glass-ceramic matrix composites for bone-tissue regeneration were produced in the form of highly porous foams utilizing the 'polymer-derived ceramics' (PDCs) approach. More precisely, two different commercial silicone polymers (a poly-methyl-siloxane, MK, and a polymethyl-phenyl-silsesquioxane, H44), reacting with suitable Na2 O, CaO, and P2 O5 yielding fillers were considered. The reaction was designed to yield products resembling Biosilicate® glass-ceramic i.e. Na2 CaSi2 O6 embedded in a silico-phosphate glass matrix. Subsequently, the samples were heat treated either in the air or in the N2 atmosphere, implying improvements in the mechanical properties and providing extra functionality. The pyrolysis in an inert atmosphere led to composites comprising a carbon phase, which promoted the absorption of infrared radiation. Such functionality makes the obtained composites promising in the perspective of disinfection of bone-tissue implants and photothermal therapy.